1997
DOI: 10.1111/j.1399-3054.1997.tb01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese toxicity on leaf CO2 assimilation of contrasting common bean genotypes

Abstract: Parameters related to leaf photosynthesis were evaluated in three genotypes of common bean (Phaseolus vulgaris L.) with contrasting tolerance to Mn toxicity. Two short‐term studies in solution culture were used to assess the effect of excess Mn on CO2 assimilation in mature and immature leaves. Mn toxicity decreased total chlorophyll content only in immature leaves, with a consequent reduction of leaf CO2 assimilation. Mature leaves that showed brown speckles characteristic of Mn toxicity, did not suffer any d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…The decline of photosynthesis is considered as one of the major mechanisms constituting the toxic effects of excess Mn and is proposed as an early indicator for Mn toxicity in tobacco (Nable et al , 1988), rice (Lidon et al , 2004) and wheat (Macfie and Taylor, 1992). Reduced CO 2 assimilation induced by excess Mn was also reported for common bean (González and Lynch, 1997), deciduous broad leaved trees (Kitao et al , 1997a), and seedlings of Citrus grandis (Li et al , 2010). Interestingly, the maximum efficiency of PSII photochemistry (F v /F m ) was not substantially affected by Mn accumulation in various plant species over a wide range of leaf Mn concentrations (Nable et al , 1988; Kitao et al , 1997b; Subrahmanyam and Rathore, 2000; Hajiboland and Hasani, 2007; Doncheva et al , 2009).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The decline of photosynthesis is considered as one of the major mechanisms constituting the toxic effects of excess Mn and is proposed as an early indicator for Mn toxicity in tobacco (Nable et al , 1988), rice (Lidon et al , 2004) and wheat (Macfie and Taylor, 1992). Reduced CO 2 assimilation induced by excess Mn was also reported for common bean (González and Lynch, 1997), deciduous broad leaved trees (Kitao et al , 1997a), and seedlings of Citrus grandis (Li et al , 2010). Interestingly, the maximum efficiency of PSII photochemistry (F v /F m ) was not substantially affected by Mn accumulation in various plant species over a wide range of leaf Mn concentrations (Nable et al , 1988; Kitao et al , 1997b; Subrahmanyam and Rathore, 2000; Hajiboland and Hasani, 2007; Doncheva et al , 2009).…”
Section: Introductionmentioning
confidence: 61%
“…Interestingly, while reduced CO 2 assimilation induced by excess Mn has been reported in many species and is considered one of the major physiological effects of Mn toxicity (Nable et al , 1988; Macfie and Taylor, 1992; González and Lynch, 1997; Kitao et al , l997a; Lidon et al , 2004; Li et al , 2010), the functional integrity of the photosynthetic apparatus assessed by the maximum efficiency of PSII photochemistry (F v /F m ) did not decline as a result of exposure to excess Mn in various plant species (Nable et al , 1988; Kitao et al , 1997b; Subrahmanyam and Rathore, 2000; Hajiboland and Hasani, 2007; Doncheva et al , 2009). However, some studies have reported a substantial decrease in F v /F m as a result of excess Mn treatment in Citrus species (Papadakis et al , 2007; Li et al , 2010), rice (Lidon et al , 2004), Mn-sensitive maize (Doncheva et al , 2009), and cucumber (Feng et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Macfie and Taylor [6] reported that the photosynthetic rate per unit chlorophyll (Chl) decreased in the sensitive wheat cultivar as Mn concentration in solution increased, indicating that Mn exerted its toxic effect on both Chl content and photosynthesis per unit Chl. Mn-induced decrease in photosynthetic rate through the decrease of Chl content has also been reported for common bean [11]. In contrast, Nable et al [4] observed that the decline of photosynthesis in tobacco leaves preceded Chl degradation.…”
Section: Introductionmentioning
confidence: 69%
“…[9], rice ( Oryza sativa L.) [10], common bean ( Phaseolus vulgaris L.) [11], mungbean ( Vigna radiat a L.) [12], Alnus hirsuta Turcz., Betula ermanii Charm., Ulmus davidiana Planch. and Acer mono Maxim.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 2? toxicity diminishes carotenoid and chlorophyll contents (Clairmont et al 1986) and reduces CO 2 assimilation in leaves (Gonzalez and Lynch 1997). Moreover, acute Mn 2?…”
Section: Introductionmentioning
confidence: 99%